Pengembangan Media Poster Terintegrasi Ayat-Ayat Al-Qur’an Pada Materi Tata Surya Di SMP/MTs - Rusydi, Rusydi; Marzuki, Marzuki; Nurhayati, Nurhayati (Universitas Islam Negeri Ar-Raniry, 2024)
This research aims to design integrated poster media with Al-Qur'an verses on solar system material and to determine the feasibility of integrated poster media with Al-Qur'an verses on solar system material. This research uses Research and Development (R&D) research with a 4D model developed by Thiagarajan. The 4D model has several stages consisting of the definition stage, the design stage, the development stage, and the final stage, namely the disseminate stage. The instrument used in this research was an expert validation sheet consisting of three experts, namely learning material experts, learning media experts, and Al-Qur'an interpretation experts. The product resulting from this research is an integrated poster media with verses from the Koran on the solar system. The results of material expert validation with the content feasibility aspect were 92.5%, the presentation feasibility aspect was 96.87% and the linguistic component aspect was 90.33%, with the average total of all scores obtaining a percentage result of 93.33%. Media expert validation with design feasibility aspects of 100%, content and objective quality aspects of 88.75%, instructional quality aspects of 93.75%, and technical aspects of 100%, with an average total of all scores resulting in a percentage of 95.62%.